PEMAHAMAN KONSEP DAN KESULITAN BELAJAR MAHASISWA: STUDI LINTAS SEMESTER PADA MATERI USAHA ENERGI - Nizami Asnawi; Anggreni Indika Seprapti; Arinal Haqqo; Ana Lailaul Fitriyah; Sentot Kusairi; Parno Parno (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2020)
Understanding concepts is one of the goals of learning physics, however there are manyindications that students have learning difficulties. This study aims to determine theunderstanding of the concepts and difficulties of students in work and energy materials and tocompare the results across semesters. This quantitative study involved 152 students majoringin physics at one of the universities in Bengkulu Province. The research instrument consistedof 4 well-reasoned multiple choice questions. Data were analyzed using descriptive statistics.The reason is used for categorizing the level of understanding of student concepts. The resultsshowed that the level of understanding of student concepts was in the category of IU(Incorrect Understanding). Students are also indicated to experience difficulties in the sub-concept of energy, effort due to gravitational force, effort due to non-conservative force, andmechanical energy.